Perencanaan Arsitektur Enterprise Menggunakan Kerangka Kerja Togaf ADM Pada Dinas Perkebunan Dan Peternakan Kab. Muaro Jambi - Sasgita, Nabila; Assegaff , Setiawan (Jurnal Manajemen Sistem Informasi, 2022)
The application of enterprise architecture aims to create alignment between business and information technology for the current and future needs of organizations. The success of implementing enterprise architecture cannot be separated from how an organization plans and designs the enterprise architecture. Planning and designing enterprise architecture requires a complete and easy-to-use methodology. In this study, a case study was conducted for strategic planning of information systems by applying the TOGAF ADM method with the help of the value chain model and other modeling tools at the Plantation and Livestock Service Office of Muaro Jambi Regency. The stages of the TOGAF ADM methodology are translated into enterprise architecture modeling, namely vision architecture, business architecture, information systems architecture and technology architecture. The results of the enterprise architecture modeling with the TOGAF ADM methodology provide a basis for overcoming the problem of lack of data integration and lack of information system support for business functions.